O eurocentrismo nos programas curriculares de história do estado de São Paulo: 1942-2008 - Martins, Marcel Alves (2012)
The teaching of History in Brazil was markedly influenced by a Eurocentric paradigm of history throughout the nineteenth century until the mid-twentieth century, along the lines of the History of French Civilization. This model, together with its canonical repertoire and its Western view of the historical process was consolidated in school curricula and teaching materials. Attempts to break with this paradigm, held in the process of curriculum reform in the 1980s and 1990s were not sufficient for this model were no longer present in the curriculum of São Paulo. The discussions around the contents of the 2008 History Curriculum Proposal for the State of São Paulo disregard the production on the teaching of History of the last thirty years and point to a setback regarding the selection and content organization, rescuing the Eurocentric model curriculum school. In presenting critics on some elements that make up the Eurocentrism and analyzing the historical background (1942-2008) of knowledge in school History curricula, this research is to identify the moving object of learning content in the curriculum, its continuities or discontinuities, checking the extent to which the 2008 Proposed Structure for the State of São Paulo represents a setback in the content selection of History